Longitudinal Evaluation of Pharmacists' Social Distance Preference and Attitudes toward Patients with Opioid Misuse following An Educational Training Program. Issue 1 (December 2022) - Werremeyer, Amy; Strand, Mark A.; Eukel, Heidi; Skoy, Elizabeth; Steig, Jayme; Frenzel, Oliver
Background : Pharmacist stigma via examination of social distance preference and negative attitudes toward persons who misuse opioids is prevalent and may lower the quality of care provided to patients. Few studies have previously extended beyond the immediate post-intervention period to examine stigma change. Methods: This longitudinal cohort study utilized a pre-survey administered before the training program, a post-survey immediately upon completion of the training program, and a delayed post-survey, administered 12 months after the training program. Co-primary outcomes were changes in social distance scale (SDS) total score from baseline to post-survey and from baseline to 12 months. Secondary outcomes included change in SDS question scores and change in negative attitudes. One hundred eighty-seven of the 1211 eligible pharmacists in the state completed the training. Matched responses of forty-four pharmacists who completed all three surveys were examined. Results: The mean total SDS score was significantly lower in the immediate post-training survey than the pre-training mean (14.75 vs. 16.57, p  = .000). The 12 months mean total SDS score was also significantly lower than the pre-training mean (15.32 vs. 16.57, p  = .017). Significant changes in negative attitudes from baseline to post-survey and from baseline to 12 months were seen. Conclusion: Stigma reduction components integrated into opioid training decreased pharmacist social distance preference and negative attitudes toward patients who misuse opioids immediately after the training and, most notably, were sustained for 12 months.